The Importance of Religious Moderation-Based Islamic Economic Education to the Community for the Realization of Economic Justice in Indonesia - Jefik Zulfikar Hafizd (Rumah Moderasi Beragama of Syekh Nurjati State Islamic Institute Cirebon, 2022)
Abstract: Indonesia is a country with a majority Muslim population and has great Islamic economic potential. National development goals are oriented toward the creation of a just and prosperous society, this goal can be achieved by an economic system based on sharia principles. Although it has great potential, the Indonesian people do not yet have sufficient literacy about Islamic economics. Religious moderation is needed in the public education process so that literacy positively impacts the sharia economy. The concept and practice of Islamic economics still require development and are not free from shortcomings that make it not fully in accordance with Islamic law. People who have good sharia economic literacy will behave in a moderate manner, namely accepting the idea of ​​sharia economics with its various shortcomings while still trying to push towards a better direction from its compatibility with Islamic law and its existence in the economy. Keywords: Education; Sharia Economics; Religious Moderation; Economic Justice; Indonesia Abstrak: Indonesia merupakan negara dengan mayoritas penduduk beragama Islam memiliki potensi ekonomi syariah yang besar. Tujuan pembangunan nasional berorientasi pada terciptanya masyarakat adil dan makmur, tujuan ini dapat dicapai oleh sistem ekonomi yang berlandaskan prinsip syariah. Meski memiliki potensi besar, namun masyarakat Indonesia belum memiliki literasi yang cukup tentang ekonomi syariah. Moderasi beragama diperlukan dalam proses edukasi masyarakat agar literasi yang dimiliki memberikan dampak positif bagi ekonomi syariah. Konsep dan praktek ekonomi syariah masih memerlukan pengembangan dan tidak luput dari kekurangan yang menjadikannya tidak sepenuhnya sesuai dengan syariat Islam. Masyarakat yang memiliki literasi ekonomi syariah baik (well literature) akan bersikap secara moderat yakni menerima gagasan ekonomi syariah dengan berbagai kekurangannya dengan tetap berusaha untuk mendorong ke arah yang lebih baik dari kesesuaiannya dengan syariat Islam dan sisi eksistensinya dalam perekonomian. Kata kunci: Edukasi; Ekonomi Syariah; Moderasi Beragama; Keadilan Ekonomi; Indonesia